Eksistensi Akta Notaris Dalam Penguatan Legalitas Kelembagaan Pendidikan Anak Usia Dini - Agus Muslim (Universitas Islam Indonesia, 2017)
AbstractThe main problem in this study is the first, how the existence of a notarial deed in strengthening the legality of the implementation of the Early Childhood Education institutions (ECD) in Sukabumi? And secondly, what form of certificate of incorporation institutions Early Childhood Education (ECD) in Sukabumi ?. This research is empirical or sociological law by using an empirical approach / sociological approach to law (statute approach). The results showed the existence of a notarial deed is very important for the implementation of ECD in Sukabumi, because the activities of early childhood institutions is closely linked to the public. So it is not enough just to their form of recognition (justification) in the form of early childhood Operating License issued by the Department of Education alone, but requires that the (legality) in the form of a notarial deed. Based on the research results are to some ECD Institutions authors found no notarial deed in the form of legal entities association deed, and the deed of the institution, but as with all forms of legal entity foundation deed.Keywords: Deed, foundations, associations, ECD